(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
This article deals with human rights and their institutional spheres in Islamic law. It is impossible to imagine the practical protection of human rights without international institutions and basic international documents. The legal status of international institutes on human rights and the content of the main international documents will determine the requirements and mechanisms for the protection of human rights. Human rights occupy an important place in Islamic teachings. We can see that great thinker such as Majduddin Muhammad Usturshani, who lived in Transoxiana (Mowaraunnahr) in the Middle Ages, were the authors of the first fundamental work on “Child’s Rights” three centuries before Western scholars. Majduddin Mohammad further increases the scientific value of Usturshani’s work, turning it into a unique source in the history of the formation of the scientific direction of juvenile law, that is, children’s rights, which is one of the important segments of human rights.